Synthesis and Characterization of Some New Pyrazole Derivatives - Nisreen H. Kar (Journal of Global Pharma Technology, 2019)
This work contain many steps starting from esterification of  isophthalic acid to yield diester compound [I] which was converted to their acid hydrazide [II], then the later compound reacted with ethylacetoacetate  to  yield pyrazol-5-one compound [III]. Afterword added acetyl chloride to give the compound [IV], the reaction of this compound with theiosemicarbazide led to produce a new carbothioamide compound [V], which was reacted with ethyl chloro acetate to yield the thioxoimidazolidin compound [VI]. The condensation reactions of this compound with different substituted aldehyde give new alkene derivatives [VII] a-d. The synthesized compounds were characterized by melting points, FT-IR, 1H-NMR and Mass spectroscopy.Keywords: Pyrazole, Heterocyclic, Isophthalic acid, Acid hydrazide, Alkene derivatives.